Optimization Existence Bumdes as Supporter Economy in Village Angantaka Badung - PUTRI, Putu Yudha Asteria; SAPUTRA, Komang Adi Kurniawan; SANTINI, Ni Made (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
You  will  experience  problems  or  obstacles  in  running  every  business  that executes  suitable  business  trading  or  service.  Body  business  owned  by  village Which  called  with  BUMDes  aims  as  mover  economy  village and  well-being public  village.  Village  Angantaka  Regency  Badung  is  the  Wrong  village  That owns BUMDes as a supporter of its economy. BUMDes Chess Eka Amertha has several  business  units:  shops,  credit  loans,  bicycle  loans,  and  motorcycle  loans. BUMDes Chess Eka Amertha has a chance to enhance the well-being of the public village. There is still a constraint in its implementation, which is experienced and related to understanding accountancy simple and system management company. Group 33 KKN-PMM Angantaka Village in 2024 will carry out approaches and solutions to the problems associated with BUMDes governance to make BUMDes Village  Angantaka  an  institution  that  stands  sustainably.  Activity  PMM  KKN consists of a presentation of a paper about orderly financial administration and corporate  governance.  Implementation  method the  activity  consists  of  several stages: Preparation, Training, Adjustment and Evaluation. Based on the results of discussions with participants, participants were very grateful to the Warmadewa University  PMM  KKN  Group  because  it  can  solve  classic  problems.  Problem regarding  the  expected  preparation  of  report  finance:  No  appear  Again,  and accountability can be held appropriately.